Vocal recognition suggests premating isolation between lineages of a lekking hummingbird. (23rd May 2020) - Cruz-Yepez, Nataly; González, Clementina; Ornelas, Juan Francisco
Abstract: Species with genetically differentiated allopatric populations commonly differ in phenotypic traits due to drift and/or selection, which can be important drivers of reproductive isolation. Wedge-tailed sabrewing ( Campylopterus curvipennis ) is a species complex composed of three genetically and acoustically differentiated allopatric lineages that correspond to currently recognized subspecies in Mexico: C. c. curvipennis (Sierra Madre Oriental), C. c. pampa (Yucatán Peninsula), and C. c. excellens (Los Tuxtlas). Although excellens is taxonomically recognized as a distinct species, there is genetic evidence that lineages excellens and curvipennis have diverged from each other later than pampa . In this study, we experimentally tested C. c. curvipennis song recognition as a major factor in premating reproductive isolation for lineage recognition. To this end, we conducted a song playback experiment to test whether territorial males of one C. c. curvipennis lek discriminate among potential competitors based on male songs from the three lineages. Males of curvipennis responded more aggressively to songs of their own lineage and excellens, than to songs of the most divergent lineage pampa, as evidenced by significant differences in a variety of intensity and latency response variables. This indicate that the pampa male song does not represent a competitive threat as curvipennis and excellens songs, in which divergence and song recognition represent premating reproductive isolation between these isolated lineages. However, the acoustic limits between curvipennis and excellens might be attenuated by gene flow in case of secondary contact between them, despite the strong and relatively rapid divergence of their sexually selected song traits. Abstract : In birds, divergence in characters involved in mate choice, such as song, can play a role as premating isolation barriers. With playback experiments, we showed that males of a lekking hummingbird responded with different intensity to the songs of lineages with varying degrees of genetic differentiation and time since isolation. Our results suggest that the song of these hummingbirds can be a mechanism that prevented mating on secondary contact between genetically differentiated lineages.